Low Molecular Weight Heparin Induced Liver Toxicity (Revista de Medicina Clinica, 2021)
Low-molecular-weight heparins (LMWH) are the drugs of choice in the prophylaxis and initial treatment of thromboembolic disease, as well as maintenance therapy in patients who are not candidates for oral anticoagulation1,5,6. They are anticoagulant drugs of indirect action, the mechanism of action of which lies primarily in anti-Xa activity, presenting a less intense inhibitory effector on factor IIa1,2. Its half-life is longer than that of HNF, presenting high availability, which is why it is administered subcutaneously in one or two doses per day, presenting its maximum peak of activity at 3-4 hours with rapid subsequent drop. Its route of elimination is exclusively renal, so caution must be exercised in its dosage in patients with moderate and severe renal insufficiency.Among the side effects described are: bleeding, urticarial reaction, heparin-induced thrombocytopenia (HIT), osteoporosis, and even skin necrosis2,5. Compared with HNF, it presents fewer bleeding complications, with no differences in the incidence of HIT. Another not infrequent effect is liver toxicity, which occurs in up to 9% of patients treated with LMWH depending on the series, in most cases without associated symtoms1,5.We present the case of a patient with hepatotoxicity in the context of treatment with low molecular weight heparin, this being a diagnosis of exclusion after ruling out other possible etiologies and who presented resolution of the condition after the suspension of LMWH.
Keywords: Low molecular weight heparins; hepatotoxicity; heparin adverse reactions